The Role of Network Security in Class Conference During COVID-19 Pandemic - Ivan Sebastian Edbert; Julio Pramaitama; Kevin Tio; Muhammad Rizky; Alvina Aulia (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
Security is crucial for the network. But there are still system leaks, especially in class conferences during the pandemic. Because of a lot of data exchange and data entry, some viruses are difficult to identify. So, the role of network security is vital. Many viruses spread through links, and others can access cases of misuse of links; the issue is called Zoom bombing. So, from managing the instability of data in and out of conference classes during this pandemic, many activities are carried out online that awareness of more comprehensive network security. With the COVID-19 pandemic, class conferences are prevalent in today’s world. Millions of people use it for various reasons, and one of them is for education. However, there are issues related to the network’s security where users’ data was stolen and impersonated or network trafficking, which will cause fault and disruption in the network. This research have 3 methodologies include Systematic Literature Review, Research Questions (identify the focus of the literature review, which helps process the data more clearly), Result Finding (the study of an existing paper with specific keywords to answer the research questions). As the result, it can be concluded that there are many ways to prevent attacks by improving the network’s security such as network security defense mechanisms and firewall. So that everything can be petrified in terms of comfort in meet conferences so that class conferences activities can run safely.